TINJAUAN PEMBUDAYAAN KITAR SEMULA DALAM KALANGAN PELAJAR â€œTECHNICAL VOCATIONAL EDUCATION AND TRAININGâ€ (TVET) - Mior Ahmad Noor, Mior Amran Noor; Abd Hamid, Azhar (Journal of Techno-Social, 2013)
Recycling is an effort to collect, process and reuse the things that have been used. This descriptive research was done to find out the recycling practice among â€œTechnical Vocational Education and Trainingâ€ (TVET) students. The focus of this research is to identify studentsâ€™ prior knowledge on nature, recycling practice among Bandar Penawar Community College students and to identify ways to increase the awareness level among Bandar Penawar Community College students. This research uses survey instruments. The descriptive and interpretive statistics with frequency, percentages, mean and standard deviation that was obtained was analyzed using Statistical Packages for Social Sciences (SPSS) version 20. The sample of this research involving respondents consists of Bandar Penawar Community College students. The instrument used in this research is in the form of survey that consists of four items regarding to the background of the respondents and questions related to the research questions. Based on the findings of the research, most of the respondents gave positive perceptions on the recycling practice. This shows that the respondents are aware of the importance of recycling for the benefits of the community generally. Everyone should create and make an effort to recycle to help preventing from disasters to the human beings. Hence, recycling of the waste such as papers, cans, newspapers and others is one of the preservation and conservation of nature.